CONTENT OF PHYSICAL EDUCATION OF CHILDREN OF DIFFERENT AGES AND WAYS OF ITS ORGANIZATION (FOR EXAMPLE OF CHILDREN AGED 4-6) - Uraimov Sanjar; Abdurahimova Hayotxon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides information on the form and content of physical education of children in preschool education, which provides for the provision of workloads, taking into account the capabilities of children.